Brasil - Argentina e o Sistema Regional de Salvaguardas Nucleares - Aguilar, Sérgio Luiz Cruz [UNESP] (2013)
In 2011, the Brazilian-Argentine Agency for Accounting and Control of Nuclear Materials (ABACC), created to administer the Common System of Accounting and Control of Nuclear Material (CSAC) has completed twenty years of existence. ABACC and the Quadripartite Agreement established with International Atomic Energy Agency (IAEA) are a special system of safeguards that presents itself as an important example of regional contribution to global nuclear proliferation. The paper presents some considerations about the process of understanding between Brazil and Argentina that resulted in the creation of ABACC, indicates succinctly some theoretical explanations of international relations for this process and, from some features of the Agency, relates how the ABACC experience could support nuclear weapons free zones.